TÜRK-İNGİLİZ İLİŞKİLERİ (1939?1945) - ÖZTOP, FATMA ANIL (Fırat Üniveristesi, 2010)
16. Yüzyılda başlayan Türk-İngiliz ilişkileri, bugüne kadar inişli çıkışlı bir grafik izlemiştir. 1877?1878 Osmanlı-Rus Savaşı'na kadar Osmanlı'nın toprak bütünlüğünü koruma politikası izleyen İngiltere, bu tarihten sonra Osmanlı'yı parçalama siyaseti izleyeme başlamıştır.İngiltere'nin bu politikası, Lozan Antlaşması'na kadar devam etti. Lozan Antlaşması ile İngiltere, Anadolu'da kurulan yeni Türk devletini tanıdı. Lozan'dan kalan Musul sorunun 1926'da çözülmesiyle birlikte Türk-İngiliz ilişkileri, II. Dünya Savaşı'na kadar yumuşama dönemine girdi.Türkiye, Osmanlı İmparatorluğu'nun parçalanmasının ardından miras aldığı Anadolu topraklarında üç yanı sorun yumağı olan Balkanlar, Ortadoğu ve Kafkaslar arasında, savaş sonrası ekonomisini rayına oturtmaya çalışırken, ufukta beliren savaş bulutlarını endişe ile takip etmiştir. Savaş patlak verdiğinde her iki taraf da stratejik öneme sahip Türkiye'yi yanına çekmeye çalışmıştır.Türkiye, II. Dünya Savaşı'nın son yılına kadar tüm zorlamalara direnerek savaş dışı kalmayı başarmış ancak savaş dışı durumunu sürdürmesi kolay olmamıştır. Savaşın genel gidişi ve stratejisindeki değişikliklere uygun olarak, gerek Mihver devletleri gerekse Müttefikler zaman zaman Türkiye'nin savaşa girmesi konusunda ağır baskıda bulunmuşlardır.Anahtar Kelimeler: Türkiye, İngiltere, İkinci Dünya Savaşı, W.Churchill, İ. İnönü

Anglo-Turkish relations, which started in the 16th century, have followed a bumpy path to date. Britain pursued a policy of preserving the integrity of Ottoman soil up until the Ottoman-Russian War of 1877-1878, after which she commenced a policy of division.This policy continued until the Treaty of Lausanne, with which Britain recognized the newly-formed Turkish State. Anglo-Turkish relations entered a period of thaw which continued up to the Second World War with the resolution of the Musul problem which had been a matter of dispute since Lausanne.While putting right its economy after war in the inherited Anatolian territory after the break-up of the Ottaman Empire between the Balkans, Middle East and Caucasians where three sides are problematic, Turkey followed the war pending with concern. When the war erupted both sides tried Turkey that had a strategic importance to be on its side.The Allies particularly England saw the Turkish army as a rich source of soldier and thought to utilize this source ideally. According to the plans of England, Turkey would join the battle directly. But in 1943 this thought changed in the direction of opinions of the Americans, Russians and England transformed the emphasis into the opening of the airforce bases to usage and to see them as a bridge in the transport of logistic support and concantrated its pressure in this direction.Turkey had succeded in staying out of the war by standing out against all forces until last year of the Second World War because it was Allied with one of the warning groups namely England and France although it wasn?t joined the war actually it was on the side of Allied Powers.It was not easy to continue the condition of being out of the war for Turkey. In acordance with the general course and the changes in the strategy of the war, either Axis Powers or Allies occasionally pressured Turkey heavily to goto the war. Despite these pressures the governers of Turkey endeavoured to pass these annoying years with minimal loss by using balance policy and deleying tactics.Key Words: Turkey, Britain, The Second World War, W. Churchill, İ. İnönü
Turkish - Anglo relations (1939-1945)
Keywords: Tarih; Uluslararası İlişkiler